The influence of braking time on heat flow through the friction surfaces of the friction elements of disk brakes for railway vehicles - Bocîi, Liviu S. (Transport, 2011)
Disk brakes were first introduced on the suburban and urban coaches and high speed freight cars (V > 120 km/h) for the following reasons: shoe brakes reached their potential limits, especially at high speeds; the maintenance of disc brakes is cheaper; greater comfort; the friction coefficient of disk brake elements (friction pad and brake disc) presents lower variation in velocity and pressure; disk brakes present lower temperatures of friction surfaces. The determination of uniform heat flow through the friction elements of disk brakes is very important since the early designing stage. Such way one avoids overheating both disk brakes and friction pads that may result when the physical properties (chemical and mechanical) of materials are not correctly matched and have negative effects on braking efficiency (small coefficient of friction, large braking distance etc.) This work studies the influence of braking time (30 s, 40 s, 50 s, 60 s) on the uniform heat flow of the friction element surface. Note that in the same area of disk brake friction 0.4 m2, heat flow decreases with an increased duration of braking, leading to longer braking space. At the same time, if pressure on the pad of disk brake friction decreases, heat flow increases. First Published Online: 12 Apr 2011